Argumentation of the complex scheme for diagnosis and treatment of mastopathy in dogs - V. L. Khomutenko; D. D. Bilyi (Theoretical and Applied Veterinary Medicine)
Over the past 3 years, a 1.7-fold increase in the incidence of cystic fibrosis in bitches has been recorded. Currently, the problems of early diagnosis of mastopathy and effective treatment of mastopathy, which is one of the ways to reduce the incidence of mammary gland tumors in bitches, have become particularly relevant. The purpose of the research was the development and clinical approval of schemes for complex diagnosis and treatment of bitches with mastopathy. The clinical significance and relationship of the diagnostic criteria for mastopathy in bitches was determined, which became the basis for the substantiation of the diagnostic protocol of fibrocystic disease, which includes a step-by-step analysis of anamnestic data, the results of clinical, ultrasonographic, radiological, histological / cytological research, as well as an assessment of hormonal status and level expression of tumor markers. At the same time, the level of mammary gland tumor markers (carcinoembryonic - CEA and cancer antigen - CA 15-3) makes it possible to exclude the presence of benign and/or malignant neoplasia in other mammary glands. In the absolute majority of cases, nonproliferative histological type (80%) and diffuse form (88.3%) of mastopathy are diagnosed. Among the accompanying diseases, 60.3% have pathologies of the reproductive tract, 18.8% - kidneys and urinary tracts, 12.5% - digestive organs. The clinical feasibility of including Metformin in the therapeutic protocol (Tamoxifen, Dostinex, Indole 3-carbinol OS, Vobenzym, Hepavi-kel) is confirmed by a 9% increase in the effectiveness of treatment against the background of speeding up the recovery period, reducing the risk of further progression and lengthening the period before its onset. The proposed scheme ensured the restoration of follicle-stimulating hormone, progesterone, extradiol and prolactin levels after 4 weeks, while in animals of the control group - only after 8 weeks. The prospect of further research is a more detailed study of the possibilities of using the proposed protocol in oncology practice.